Healing of Fresh Extraction Sockets Filled with Bioactive Glass Particles: Histological Findings in Humans. (12th June 2012) - Clozza, Emanuele; Pea, Maurizio; Cavalli, Fabio; Moimas, Loredana; Di Lenarda, Roberto; Biasotto, Matteo
ABSTRACT Purpose: The aim of the present study was to histologically evaluate fresh human sockets filled with bioactive glass after 6 months of healing. Materials and Methods: In 13 patients, 32 single extraction sites in the anterior area underwent socket ridge preservation procedure (RPP) with a bioactive glass (BioRestore™, Inion Oy, Tampere, Finland). At implant installation, 22 bone cores were trephined out and processed for histomorphometric and immunohistochemical analysis. Results: Newly formed immature bone around residual particles of bioactive glass was found in all 22 biopsies. The histomorphometry of the amount of bone, provisional matrix, and residual graft returned a mean ± SD value of 54 ± 31%, 37.9 ± 25.6%, and 8.1 ± 7.8, respectively, 6 months after RPP. Conclusion: The use of this grafting material in fresh extraction sockets appears to delay the healing processes of the alveolar bone; therefore, its indication as a material for RPP when implant placement is considered within 6 months after extraction should be revised.